Locating Transcendence in Japanese Minzoku Geinô: Yamabushi and Miko Kagura - Kuly, Lisa (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2003)
AbstractContemporary minzoku geinô (folk performing arts) in Japanese society is associated with the matsuri, or festival. Community members, such as workers and students, practise and perform various types of minzoku geinô in preparation for local festivals. However, a look at the history of minzoku geinô reveals that originally its practitioners were marginalized members of society, who used ecstatic expression to perform various rites such as healings, exorcisms, and blessings. Furthermore, the attitude toward ritual specialists was often negative; indeed, shamanistic practices were prohibited during the Meiji period (1868-1912). In response to social attitudes, ecstatic performers of Japan’s premodern period negotiated their expressive powers in a variety of ways in order to survive. This article introduces the reader to the typology of minzoku geinô that involves ecstatic performance presented by yamabushi, male mountain-dwelling ascetics, and miko, female shamans generally associated with Shinto shrines. Moreover, the discussion in this paper illustrates how ecstatic performance changed throughout history to the extent that it is now seldom performed by marginalized ritual specialists. Performers of contemporary minzoku geinô are accepted members of society. Furthermore, both the performers and the audience of minzoku geinô are affected by the transformative nature of ecstatic expression.